Nitaqat Program and Decree Saudi Nationality's Effects on Work Interest Mediated by Salary Range - Dilal Adlin Fadi (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
The purpose of this study was to test and analyze the influence of the national Nitaqot and SK schemes on the working interest of pharmacists, test and analyze the effect of the national Nitaqot and SK schemes on the salary range, test and analyze the mediating impact of the wage range in the Nitaqot program on the working interest of pharmacists and to test and analyze the influence of Saudi national decisions mediating wage ranges on pharmacist job interest. This study uses a type of quantitative research that will test the hypothesis (correlation). The research samples are individual pharmacists who are employees at the existing Directorate of Operations of Kimia Farma Dawaa. Co.Ltd in 2021. This research uses a non-probability sampling technique because there is little research time, and the research costs are not high. H1 - The Nitaqot program has a negative impact on the working interest of pharmacists H2 - The Saudi national decree has a positive effect on the working interest of pharmacists H3 - The Nitaqot program has a positive impact on the salary range H4 - The Saudi national decree has a positive effect on the wage range H5 - Salary range has a positive impact on the Pharmacist's Job Interest H6 - The salary range mediates the Nitaqot program against the working interest of pharmacists H7 - The Saudi state's decision to mediate the Nitaqot scheme against the work interests of pharmacists